HUBUNGAN POSTUR KERJA DAN DURASI KERJA DENGAN KELUHAN NYERI OTOT PADA PEKERJA PABRIK TAHU X DI KOTA SEMARANG - Rebecca Olivya Putri; Siswi Jayanti; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2021)
Complaints of muscle pain are pain, heaviness, stiffness in the muscles and it can be experienced in the neck, shoulders, back, waist and other parts of the body. Generally, people who feel complaints of muscle pain originate from habits they do during work. Complaints of muscle pain can arise as a result of inappropriate work posture and a long duration of working. This study aims to analyze the correlation between work posture and work duration with complaints of muscle pain at tofu X factory workers in Semarang City. This type of research is quantitative with a cross-sectional study. The sample of this research is the entire population, namely 24 workers. The research instrument is REBA (Rapid Entire Body Assessment) sheet for measuring work posture variables, the questionnaire sheet for work duration variables, NBM (Nordic Body Map) sheet for muscle pain complaint variables. The data analysis used was the Fisher Exact Test. The analysis showed a significant correlation between both work posture (p-value = 0.040) and work duration (p-value = 0.028) with complaints of muscle pain. The present study suggested further intervention that requires both engineering and administrative control measures to reduce the high percentage of muscle pain complaints among those workers.